TOKSISITAS BIOINSEKTISIDA EKSTRAK KULIT JERUK TERHADAP KUTU LONCAT JERUK Diaphorina citri Kuwayama (Hemiptera: Psyllidae) SEBAGAI VEKTOR PENYAKIT CVPD - Susi Wuryantini; Harwanto Harwanto; Rizky Arya Yudistira (JURNAL AGRONIDA, 2019)
Diaphorina citri is an important pest in citrus plants because of its role as a vector of CitrusVein Phloem Degeneration (CVPD) disease. The study was a follow-up test of the preliminarytests carried out previously. The aim of this study was to determine the effective concentrationof bioinsecticide of Japansche Citroen (JC) orange peel extract in controlling D. citri in thephases of nymph and imago. The concentration tested was 0% (control); 0.01%; 0.1%; 1%;and 10% (v / v) with a comparison of imidacloprid insecticide 0.1%. The test results showedthat the JC citrus peel extract at a concentration of 0.1 effectively controlled the D. citri nymphstarting at 96 hours after application (HAA) with a mortality of 69%. The concentration of 1%was effective from 24 HAA with a mortality of 65% and thereafter reaching up to 100% at 120HAA, this was not significantly different from the 10% concentration treatment andimidacloprid insecticide 0.1%, yet was significantly different from other treatments andcontrols. Citrus peel extract was effective for controlling imago of D. citri on 10% concentration. The concentration that was able to provide mortality above 50% was the highestconcentration of 10% at 96, 120 and 144 HAA. The results of the probit analysis showed thatthe LC50 values at 24 HAA on nymphs was 1.86 and the LC90 value was 9.10. The treatment onimago the LC50 at 48 HAA was 21.34 and the LC90 was not achieved. The results of thecalculation of the LC50 and LC90 values showed that the value in nymphs was smaller than inimago. This showed that the bioinsecticide of JC citrus peel extract was more effective againstnymphs than imago of D. citri. Bioinsecticide of JC citrus peel extract was effective againstpsyllid nymph of D. citri at concentrations of 0.1 and 1% and against the imago phase waseffective at 10%.Keywords: Toxicity, citrus peel extract, Diaphorina citri